Linguistic devices of lenitive mitigation in journalistic communication during the Coronavirus epidemic - Tawfik Ali, Mai Morsy (Rivista Italiana di Filosofia del Linguaggio, 2024)
In this paper we analyze the mitigation strategies used in newspaper language during the coronavirus epidemic, focusing on the importance of using such strategies during this difficult period. The subject of study are the utterances proffered mostly by the President of the Republic, the prime minister, ministers, representatives of institutions, doctors or famous people reported in the articles published in la Repubblica in March 2020. We hypothesize that during the Coronavirus crisis, directive speech acts, such as command, request, prohibition, prayer, advice and invitation are frequent. These acts would have been formulated with the help of linguistic mitigators to soften the messages addressed to the Italian who were in deep mouring for the loss of a loved one. The analysis shows that mitigation is a very important phenomenon, it is used to improve communication by reducing the risk of misunderstandings, conflicts, and other negative outcomes. It is inferred from the research carried on here that the linguistic devices of lenitive mitigation on the one hand belong to different grammatical categories, and on the other hand act on different aspects of the linguistic act. Furthermore, in the most examples the mitigation comes from the combination of different linguistic devices: lexical, discursive, morphosyntactic, and textual.